Anxiety in prisoners who are currently serving a prison term: A descriptive study in a class IIA women's prison in Semarang - Bina, Maria Yoanita; Andriany, Megah; Dewi, Nur Setiawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Detention can cause problems and stressors for prisoners such as anxiety. Anxiety in female prisoners has an impact on psychological and emotional stress that causes violence in prisons. However, research related to anxiety in female prisoners is still limited to anxiety before going home. Therefore, researchers are interested in research to determine the level of anxiety in prisoners who are serving a period of detention. The purpose of this study was to determine the level of anxiety in female prisoners who are serving a period of detention. The research design used in this study was a critical study to see a picture of the anxiety level of female prisoners. The sample in this study was 128 people who were selected using a purposive sampling technique. The results showed that the highest prisoners' anxiety level was in the moderate category as much as 44.5 percent and the lowest was in the panic category as much as 5.5 percent. Female prisoner anxiety arises because of negative emotions due to problems faced, stressors, feelings of failure, and feelings of insecurity. Most of the anxiety levels of female prisoners in prison are in the medium category. Therefore, nurses need to develop research related to interventions to overcome the anxiety of female prisoners in prison. Abstrak: Penahanan dapat menimbulkan masalah dan stressor bagi warga binaan pemasyarakatan (WBP) seperti kecemasan. Kecemasan pada WBP perempuan berdampak pada tekanan psikis dan emosional yang menimbulkan kekerasan dalam lapas. Namun, penelitian terkait kecemasan pada WBP perempuan masih terbatas pada kecemasan menjelang pulang. Oleh karena itu, peneliti tertarik untuk melakukan penelitian untuk mengetahui tingkat kecemasan pada WBP yang sedang menjalani masa tahanan. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kecemasan pada WBP perempuan yang sedang menjalani masa tahanan. Desain penelitian yang digunakan dalam penelitian ini adalah penelitian depkritif untuk melihat gambaran tingkatan kecemasan WBP perempuan. Sampel dalam penelitian ini sebesar 128 orang yang dipilih dengan menggunakan teknik purposive sampling. Hasil penelitian menunjukan tingkat kecemasan WBP tertinggi berada pada kategori sedang sebanyak 44.5% dan terendah berada pada kategori panik sebanyak 5.5%. Kecemasan WBP perempuan muncul karena adanya emosi negatif karena adanya permasalahan yang dihadapi, adanya stressor, merasakan kegagalan, dan adanya perasaan tidak aman. Tingkat kecemasan WBP perempuan di Lapas sebagian besar berada pada kategori sedang. Oleh Karena itu, perawat perlu mengembangkan riset terkait intervensi untuk mengatasi kecemasan WBP perempuan di Lapas.